Experimentally validated model of coupled thermal processes in a laboratory switchgear. Issue 11 (1st August 2016) - Bedkowski, Mateusz; Smolka, Jacek; Bulinski, Zbigniew; Ryfa, Arkadiusz; Ligeza, Maciej
Abstract : In this study, the experimentally validated model of coupled thermal processes developed for a three‐phase busbar system of a laboratory switchgear is presented. In the validation process of the mathematical model, over a hundred thermocouples were employed to measure the temperature of the busbar paths and the inner air for three switchgear ampacities of both hermetic and ventilated enclosure. In the numerical model, the fundamental thermal problems were coupled with the electromagnetic field to accurately define the Joule losses and to show the impact of the inductance phenomena on the heat generation in the busbars. Moreover, the power losses due to the busbar junctions were taken into consideration. Thus, a comparison of the available mathematical models describing the joint resistance was studied. In the sensitivity analysis, the effects of the turbulence models, the heat transfer coefficient on external walls and the busbar emissivity definitions on the unit thermal performance were presented.